Climate variability amplifies the need for vector-borne disease outbreak preparedness - William S. Hart; James W. Hurrell; Alexander R. Kaye; Meera Chand; Matt J. Keeling; Robin N. Thompson (Proceedings of the National Academy of Sciences, 2025)
In locations that do not currently experience vector-borne disease (VBD) outbreaks but may be at risk under climate change, modeling future climate suitability for transmission is important for outbreak preparedness. Uncertainty in the future climate arises from three sources—differences in emissions scenarios, structural uncertainty across climate models, and internal climate variability (ICV)—but ICV is rarely considered in climate-VBD studies. Here, we demonstrate that ICV is a key source of uncertainty in climate suitability for VBD transmission, even decades into the future. Because of ICV, suitable climate conditions for transmission may arise in many locations sooner than expected under climate change alone.